2016
DOI: 10.19148/ijhbs.65157
|View full text |Cite
|
Sign up to set email alerts
|

The Mediator Role of Internalized Homophobia and Self-Compassion on the Link between Attachment Styles and Depression in Lesbian, Gay and Bisexual Individuals

Abstract: The main purpose of this study was to investigate the mediating role of internalized homophobia and self-compassion in the relationship between attachment styles and depression among lesbian, gay and bisexual individuals. The participants of the study consisted of 886 LGB individuals whose ages range from 18 to 30 ( ̅ =22.73, Sd=3.54). In collecting the data, Experiences in Close Relationships Inventory (ECRI-II), Self-Compassion Scale, Internalized Homophobia Scale (for Gay and Bisexual men), Lesbian Internal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…In previous studies, researchers have found self-compassion to mediate the relationship between attachment styles and mental health, suggesting that individuals who exhibit insecure attachment styles (i.e., anxious and avoidant) demonstrate less of an ability to be kind to themselves, which impacts their overall mental health and well-being (Neff & McGehee, 2010; Raque-Bogdan, Ericson, Jackson, Martin, & Bryan, 2011). Findings from Set, Şimsek, and Altınok’s (2016) study support that adult attachment style is correlated to self-compassion in LGB individuals in Turkey, although self-compassion did not mediate the relationship between insecure adult attachment and depression in this study. Given the relationships between attachment and self-compassion in Set et al’s (2016) study, further research is warranted to better understand the role that social support and self-compassion may play in the well-being of LGB people in Turkey.…”
Section: The Relationship Between Social Support Self-compassion and ...supporting
confidence: 52%
See 2 more Smart Citations
“…In previous studies, researchers have found self-compassion to mediate the relationship between attachment styles and mental health, suggesting that individuals who exhibit insecure attachment styles (i.e., anxious and avoidant) demonstrate less of an ability to be kind to themselves, which impacts their overall mental health and well-being (Neff & McGehee, 2010; Raque-Bogdan, Ericson, Jackson, Martin, & Bryan, 2011). Findings from Set, Şimsek, and Altınok’s (2016) study support that adult attachment style is correlated to self-compassion in LGB individuals in Turkey, although self-compassion did not mediate the relationship between insecure adult attachment and depression in this study. Given the relationships between attachment and self-compassion in Set et al’s (2016) study, further research is warranted to better understand the role that social support and self-compassion may play in the well-being of LGB people in Turkey.…”
Section: The Relationship Between Social Support Self-compassion and ...supporting
confidence: 52%
“…The relationships among perceived social support from family, self-compassion, and well-being could be explained by attachment theory (Set & Altınok, 2016; Set et al, 2016). Parental affection and security often provide warmth and emotional support to children, which is carried to adulthood via developing self-compassion, a sense of self-worth, ability to emotionally regulate, and the capacity for intimacy with others, all essential factors to well-being (Neff & McGehee, 2010; Set & Altınok, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fear of being identified as homosexual, anxiety about rejection anxiety, and a lack of self‐confidence about the ability to deal with stigma and prejudice, which cause internalized homophobia, are the main source of stress in LGBT individuals 27 . An inability to cope, a sense of weakness and feelings of inadequacy increase the incidence of depression in LGBT individuals.…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that internalized homophobia is associated with depression and is an important risk factor for depression. Xu et al16 reported a positive correlation between internalized homophobia and depression inLGBT individuals.Fear of being identified as homosexual, anxiety about rejection anxiety, and a lack of self-confidence about the ability to deal with stigma and prejudice, which cause internalized homophobia, are the main source of stress in LGBT individuals 27. An inability to cope, a sense of weakness and feelings of inadequacy increase the incidence of depression in LGBT individuals.…”
mentioning
confidence: 99%